PENGARUH KEMITRAAN TERHADAP KEUNTUNGAN USAHA PENGGEMUKAN DOMBA DI KABUPATEN BOGOR - Muhamad Yunus; Harianto Harianto; Dwi Rachmina (Forum Agribisnis, 2014)
Bojong Jengkol Village Ciampea Bogor is the production center of male sheep. To overcome thecapital, management, and marketing problem in male sheep fattening, having a partnership with CV. Mitra Tani Farm is one of the solution for the farmer, though not all of the farmers in the village participate in the partnership.This study aims to analyse the implementation of the partnership, to describe the farming performance with descriptive analysis, and to comparethe male sheep fatteningprofitof farmers who have a partnership with Mitra Tani Farm to that ofthose who do not. The results show that the non-partnership farmer obtainesthe highest ratio of profit to cash cost per SDD per period. On the other hand, in all scale, the ratio of profit to total cost per SDD per period is negative, which can be concluded that the fattening business is disadvantaging. However, the ratio of profit to total costof the partnership  farmers better than that of non-partnership farmer since they have the smallest loss.